Thermodynamic analysis of air-compression refrigerating machine based on the exergy cost theory - Kharlampidi, Dionis; Tarasova, Victoria; Kuznetsov, Mikhail; Voytenko, Evgeniy (Eastern-European Journal of Enterprise Technologies, 2017)
On the basis of the exergy cost theory, a procedure has been developed for carrying out an in-depth thermodynamic analysis of air-compression refrigerating machines and thermal pumps taking into consideration nonequivalence of exergy losses in various links of thermotransformation process and their effect on consumption of exergy supplied to the system. A thermoeconomic model of a single-stage air-compression refrigerating machine was proposed which takes into consideration structural and topological features of the process scheme and interrelation between its elements. For an equivalent mapping of structural and topological features of the refrigerating machine scheme, a parametric flow graph was developed. The procedure uses a matrix form of recording exergy balances which is the most convenient for representation of the thermoeconomic models. In order to obtain reference operating mode of the refrigerating machine, the principle of thermodynamic process idealizing was used. Application of the structural theory of thermoeconomics has made it possible to establish the portion of endogenous and exogenous destruction of exergy in the elements of the refrigerating machine. Numerical implementation of the proposed procedure has made it possible to reveal influence of internal irreversibility in the cycle determined by non-isentropic compression processes in the compressor and expansion in the expander. A significant effect of efficiency of the expansion process in the expander on the exergy efficiency of the air-compression refrigerating machine was established. Influence of the change of ambient temperature on the character of consumption of exergy by each element of the refrigeration machine was estimated. It has been revealed that even a slight change of the ambient temperature significantly affects consumption of “fuel” by each element of the system, while the dependence is linear. Generalized dependences of exergy indicators on variable factors have been obtained which enabled finding of unfavorable operating conditions for equipment with increased energy consumption. It was established that the efficiency factor of the turboexpander has the greatest influence on the change of consumption of exergy of “fuel” in the system.